HAK KEWARISAN SUAMI DALAM PERNIKAHAN SEMANDA PADA MASYARAKAT HUKUM ADAT LAMPUNG SEBATIN - Zuhraini, Zuhraini (ASAS, 2018)
The Sebatin Lampung customary law community, seen from the lineage system including genealogical customary law community, draws on the patrilineal lineage. In the marriage system using an honest marriage system, where the wife is included in the husband's relatives. But for certain reasons, the Semanda marriage system was also used by the Sebatin Lampung customary law community. In the marriage system, the husband follows or is in the environment of his wife's relatives. In semanda marriage, which has more role in the inheritance dominated by the wife because the assets managed are indeed owned by the wife's family. If they get shared assets during the marriage, is there a husband's right to joint property in the distribution of inheritance. Based on the above background, the problem in this paper is how the distribution of inheritance in the Sebatin Lampung customary law community and how the husband's inheritance rights in Semanda marriage Sebatin Lampung Customary Law Community. The first research objective was to analyze the distribution of inheritance rights in Sebatin Lampung Customary Law Society. Second, to examine and analyze the husband's inheritance rights in the marriage of SemandaSebatin Lampung Customary Law Society. The method in this study, seen from its type, is qualitative research, even if seen from the nature of this research is library research. Data analysis using qualitative descriptive. The conclusion obtained in this study is First, For the Sebatin Lampung customary law community, inheritance system uses a system of major inheritance. This means that inheritance will fall on the oldest son. Assets inherited to the oldest sons are inheritance, customary titles, and parental property which is the result of the parents' efforts while still alive. Second, the distribution system of inheritance for husbands who carry out semi-marriages at the Sebatin Lampung customary law community, carried out in accordance with the conditions and conditions of each family. This division can be seen from two conditions. If in the family there are children born in semanda marriage, then the inheritance of the wife is given to the eldest son and the oldest child will take the policy to share or give part to his younger siblings. If there are no children, the inheritance is taken over by the wife's family while the husband does not get a shareKeywords: husband's inheritance rights, semanda marriage and sebatin Lampung customary law community.